The continental shelf off the Guadiana estuary - Mendes, Isabel (2017)
The Continental shelf is the seafloor area around a large land mass where the sea is relatively shallow compared with the open ocean.This major physiographic domain is comprised between the shoreline and the shelf break located at variable water depths (generally, around 200 m water depth) and variable extensions (average width of about 80 km). The continental shelf off the Guadiana estuary is the area in front of the Guadiana River mouth,which is influenced by the discharges of the Guadiana River Basin.This area is located in the southern border between Portugal and Spain, in the middle part of the northern Gulf of Cadiz continental shelf, southwestern Iberian Peninsula.